Preparation and electrochromic/energy storage properties of vanadium doped tungsten oxide nanowires - ZHANG Zuosheng; ZHANG Yong; DONG Senyu; CHEN Chuansheng; WANG Yong (Cailiao gongcheng, 2023)
The ionic radius of V element ion, which is in the same group as Nb, is slightly smaller than that of W ion. Doping V element can improve the ion diffusion rate and structural stability of tungsten oxide nanowires. V-doped tungsten oxide nanowire films were prepared by magnetron sputtering and hydrothermal methods. The effects of different V doping levels on the morphology, composition, and electrochromic properties of samples were investigated using field-emission scanning electron microscopy, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and electrochemical measurement equipment. The results show that the optical properties of samples are improved by appropriate V doping. When the V doping level is 0.1% (atom fraction), the tungsten oxide film exhibits the best electrochromic performance. Factors such as interplanar spacing, strengthening of V—O bonds and oxygen vacancy concentration are key factors affecting the electrochromic performance of tungsten oxide films. This work will provide useful references for the study of V-doped tungsten oxide nanowire structures as electrochromic materials and devices.